Prolonged Supplementation of Ozonated Sunflower Oil Bestows an Antiaging Effect, Improves Blood Lipid Profile and Spinal Deformities, and Protects Vital Organs of Zebrafish (Danio rerio) against Age-Related Degeneration: Two-Years Consumption Study - Kyung-Hyun Cho; Ashutosh Bahuguna; Dae-Jin Kang; Ji-Eun Kim (MDPI AG, 2024)
Ozonated sunflower oil (OSO) is renowned for its diverse therapeutic benefits. Nonetheless, the consequences of extended dietary intake of OSO have yet to be thoroughly investigated. Herein, the effect of 2-year dietary supplementation of OSO was examined on the survivability, obesity, skeletal deformities, swimming behavior, and liver, kidney, ovary, and testis function of zebrafish. Results showed that the zebrafish feed supplemented with 20% (wt/wt) OSO for 2 years emerged with higher survivability and body weight management compared to sunflower oil (SO) and normal diet (ND)-supplemented zebrafish. Radio imaging (X-ray)-based analysis revealed 2.6° and 15.2° lower spinal curvature in the OSO-supplemented groups than in the SO and ND-supplemented groups; consistently, OSO-supplemented zebrafish showed better swimming behavior. The histology analysis of the liver revealed the least fatty liver change and interleukin (IL)-6 generation in the OSO-supplemented group. Additionally, a significantly lower level of reactive oxygen species (ROS), apoptotic, and senescent cells were observed in the liver of the OSO-supplemented zebrafish. Also, no adverse effect on the kidney, testis, and ovary morphology was detected during 2 years of OSO consumption. Moreover, lower senescence with diminished ROS and apoptosis was noticed in the kidney and ovary in response to OSO consumption. The OSO supplementation was found to be effective in countering age-associated dyslipidemia by alleviating total cholesterol (TC), triglycerides (TG), low-density lipoproteins (LDL-C) and elevating high-density lipoproteins (HDL-C)/TC levels. Conclusively, prolonged OSO consumption showed no adverse effect on the morphology and functionality of vital organs; in fact, OSO supplementation displayed a protective effect against age-associated detrimental effects on spinal deformities, vital organ functionality, cell senescence, and the survivability of zebrafish.